Anti-Inflammatory Effects of Ginsenoside Rg3 via NF-κB Pathway in A549 Cells and Human Asthmatic Lung Tissue. (27th December 2016) - Lee, In-Seung; Uh, InJoon; Kim, Ki-Suk; Kim, Kang-Hoon; Park, Jiyoung; Kim, Yumi; Jung, Ji-Hoon; Jung, Hee-Jae; Jang, Hyeung-Jin
Abstract : Objective . There is limited information of the anti-inflammatory effects of Rg3 on inflamed lung cells and tissues. Therefore, we confirmed the anti-inflammatory mechanism of ginsenoside Rg3 in inflamed human airway epithelial cells (A549) and tissues whether Rg3 regulates nuclear factor kappa B (NF- κ B) activity. Methods . To induce the inflammation, IL-1 β (10 ng/ml) was treated to A549 cells for 4 h. The effects of Rg3 on NF- κ B activity and COX-2 expression were evaluated by western blotting analysis in both IL-1 β -induced inflamed A549 cell and human asthmatic airway epithelial tissues. Using multiplex cytokines assay, the secretion levels of NF- κ B-mediated cytokines/chemokines were measured. Result . Rg3 showed the significant inhibition of NF- κ B activity thereby reduced COX-2 expression was determined in both IL-1 β -induced inflamed A549 cell and human asthmatic airway epithelial tissues. In addition, among NF- κ B-mediated cytokines, the secretion levels of IL-4, TNF- α, and eotaxin were significantly decreased by Rg3 in asthma tissues. Even though there was no significant difference, IL-6, IL-9, and IL-13 secretion showed a lower tendency compared to saline-treated human asthmatic airway epithelial tissues. Conclusion . The results from this study demonstrate the potential of Rg3 as an anti-inflammatory agent through regulating NF- κ B activity and reducing the secretion of NF- κ B-mediated cytokines/chemokines.